ANALYSIS OF EYE LENS EFFECTIVE DOSE OF WORKERS DURING CARDIAC CATHERIZATION EXAMINATION IN A CATHLAB ROOM - Eka Putra Syarif H; Sriyatun Sriyatun; Gando Sari; Guntur Winarno; Ary Sasongko; Samsun Samsun (HIMNI, 2022)
In the current era, many radiological imaging technologies are used, one of which is the C-Arm equipment technology, which is capable of imaging three-dimensional patient objects in real time using fluoroscopy techniques. This study aims to obtain and evaluate the effective radiation dose received around the eye organs of radiation workers during cardiac catheterization. The main tool uses the C-Arm modality, and the TLD detector chip. The object of observation is the area around the eye organs of radiation workers consisting of one doctor and one nurse. Catheterization was carried out on 10 patients with different examination times. Research results: in the area around the eyes without protective glasses; the effective dose received by doctors' eyes ranges from 0.0011 to 0.0054 mSv, while for nurses it ranges from 0.0010 mSv to 0.0025 mSv. It was found that the effective dose received around the eye organs was lower than the dose value set by Perka Bapeten No. 8 of 2011 which is 20 mSv and ICRP 203 which is 500 mSv per year.